No products in the cart.

( x-2) (x+1) = (x-1) (x+3)

CBSE, JEE, NEET, CUET

CBSE, JEE, NEET, CUET

Question Bank, Mock Tests, Exam Papers

NCERT Solutions, Sample Papers, Notes, Videos

( x-2) (x+1) = (x-1) (x+3)
  • 1 answers

Aarya Singh 1 month, 2 weeks ago

(x-2) (x+1) = (x-1) (x+3) 2x+x-2x-2 = 2x+3x-x-3 x-2 = x+3x-3 x-2 = 4x-3 x-4x = -3+2 -3x = -1 x = 1/3
http://mycbseguide.com/examin8/

Related Questions

Prove that √5-√6 is irrational
  • 0 answers
Lcm of 5004
  • 0 answers
2 tan 30degree/1-tan2 30 degre
  • 0 answers
Find the roots of 2x2-8x+16
  • 0 answers

myCBSEguide App

myCBSEguide

Trusted by 1 Crore+ Students

Test Generator

Test Generator

Create papers online. It's FREE.

CUET Mock Tests

CUET Mock Tests

75,000+ questions to practice only on myCBSEguide app

Download myCBSEguide App